2003
DOI: 10.1159/000069656
|View full text |Cite
|
Sign up to set email alerts
|

‘Clonal Pluralization of the Self’: A New Form of Delusional Misidentification Syndrome

Abstract: The authors present a patient with paranoid schizophrenia, who has the delusion that he exists in plural numbers. The patient declares these doubles to be both psychologically and physically completely identical to him, and he believes ‘them’ to be in fact women. In connection with the case, the authors discuss the phenomena of reduplicative paramnesia and clonal pluralization, and they suggest introducing the psychopathological term ‘clonal pluralization of the self’ for the reported phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…1 Over the years, a variety of delusional misidentifications have been reported and added to periodically, albeit with a regularity in keeping with their rarity. Vörös et al (2003), for example, recently reported a new form of delusional misidentification-Clonal Pluralization of the Self-in which the patient believed he was being cloned, but as a woman! By far, the most prevalent conditions, however, and certainly the most represented and discussed in the literature, at least with regard to similarities and differences in aetiology and phenomenology, are the aforementioned Capgras,Frégoli,and Cotard delusions.…”
Section: Introductionmentioning
confidence: 99%
“…1 Over the years, a variety of delusional misidentifications have been reported and added to periodically, albeit with a regularity in keeping with their rarity. Vörös et al (2003), for example, recently reported a new form of delusional misidentification-Clonal Pluralization of the Self-in which the patient believed he was being cloned, but as a woman! By far, the most prevalent conditions, however, and certainly the most represented and discussed in the literature, at least with regard to similarities and differences in aetiology and phenomenology, are the aforementioned Capgras,Frégoli,and Cotard delusions.…”
Section: Introductionmentioning
confidence: 99%